Alterations in Some Haematological and Histological Parameters on Consumption of Calcium Carbide-Ripened Banana in Male Albino Mice - Kalita , Evarani; Hazarika , Pallabi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The aim of this study was to investigate the changes in several haematological and histopathological parameters in male Swiss albino mice fed on diets with calcium carbide-ripened banana. Fruits were collected from Khahigarh village, located in Raha subdivision of Nagaon district in Assam, and were artificially ripened using calcium carbide. The calcium carbide ripened banana was fed to albino mice, two times in a day for 14 consecutive days. Naturally ripened banana was used as positive control, and treated same way in another group of mice. The results showed that calcium carbide ripened banana induced significant decrease in RBCs count and Haemoglobin concentration; and significant increase in the WBCs. Histopathological observations of liver, kidney and testes also revealed the hazardous effect of the chemical. However, no genotoxic effect was observed with the chemical. The results suggest that consumption of banana ripened with calcium carbide can lower the body’s ability to resist some alterations of normal functions.